Transparent electrode capable of being attached to skin and manufacturing method thereof

By using a network of conductive materials embedded in an alcohol-soluble biocompatible elastomer matrix in wearable electronic devices and wound healing materials, the shortcomings of existing electrode materials in adhesion, biocompatibility and stability are solved, and efficient and stable skin adhesion and signal detection are achieved.

CN119522460APending Publication Date: 2025-02-25A SEN CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052190.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Electrode materials in existing wearable electronic devices and wound healing materials lack excellent adhesion, biocompatibility, transparency and conformal contact characteristics with the skin, and are easily dissolved by sweat, resulting in poor stability.

Method used

Using a network of conductive materials embedded in an alcohol-soluble biocompatible elastomer matrix, the surface of the alcohol-soluble matrix is ​​conformally attached to the skin, achieving high adhesion and transparency while avoiding dissolving by sweat.

Benefits of technology

Excellent adhesion, biocompatibility and transparency to the skin are achieved, and the stability of the electrode material is significantly improved, avoiding performance degradation caused by sweat dissolution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522460A_ABST
    Figure CN119522460A_ABST
Patent Text Reader

Abstract

The present invention relates to a transparent electrode attachable to skin, a method for manufacturing the transparent electrode, a wearable electronic device comprising the transparent electrode, and a wound healing pad comprising the transparent electrode. In accordance with an aspect of the invention, there is provided a transparent skin-attachable electrode comprising an alcohol-soluble biocompatible elastomeric matrix and a network of conductive material embedded in the matrix wherein one surface of the biocompatible elastomeric matrix is dissolved upon contact with an alcohol and conformally coated on the skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a transparent electrode which can be attached to the skin and a manufacturing method thereof. Background Art

[0002] In recent years, due to the development of the Internet of Things (IoT) and the increasing concern for happy life, attention and research on wearable electronic devices are increasing.

[0003] Note that a wound refers to a condition in which the skin and subcutaneous tissue are damaged due to external stimuli. Most wounds are minor and are able to heal naturally, but there are also chronic wounds that do not heal for 4 to 8 weeks and develop into ulcers that extend deep into the skin and subcutaneous tissue. Chronic patients with blood circulation disorders are particularly vulnerable to chronic wounds, making them easily exposed to bacteria even with small wounds, which makes it difficult to avoid secondary infections such as sepsis. In addition, dressings must be constantly changed to treat such wounds, and if the condition worsens, multiple surgical operations (e.g., tissue excision and skin grafting) are required. That is, chronic wounds not only increase the pain of patients and their guardians, but also increase the economic burden of treatment, thus making the treatment of patients increasingly important.

[0004] As research on the treatment of chronic wounds continues to progress, methods focusing on the natural healing mechanism of wounds have been proposed to apply energy such as pressure, electrical stimulation, light, and ultrasound to chronic wound sites that cannot heal naturally, thereby promoting cell migration and proliferation. Among these methods, the effectiveness of wound healing methods that apply electrical stimulation to the wound site has been confirmed by continuous cell and animal experiments. In this regard, hydrogels have been commercialized as electrode materials that are directly attached to the skin. However, hydrogel materials have low conductivity and low transparency, which makes patients feel uncomfortable from an aesthetic point of view, and there is a problem of reduced adhesion due to water evaporation.

[0005] Since electrode materials used in wearable electronic devices or wound treatment must adhere well to the body, it is very important to develop electrode materials with adhesion. In particular, for biosensors that are attached to the body to detect body movements or biological signals, it is necessary to ensure not only strong adhesion but also conformal contact with the skin. Therefore, electrode materials with excellent conformal contact properties with the skin are required. Skin-attachable electrode materials are required to have not only the property of conformal contact with the skin, but also transparency for biocompatibility and aesthetic purposes.

[0006] In order to achieve these characteristics, methods of utilizing commercial adhesives or imparting adhesiveness to the surface of the skin contact electrode while reducing the overall thickness of the device have been proposed.

[0007] However, the method of attaching the electrode to the skin using a commercial adhesive is not suitable because it has a high risk of causing skin irritation depending on the type of adhesive, and in addition, the adhesive may hinder direct contact between the electrode and the skin, thereby interfering with the detection of electrical signals.

[0008] On the other hand, thermoplastic polymers that can be dissolved in solvents are being studied as a method of imparting adhesiveness to the electrode material itself. For example, non-patent document 1 discloses a method of providing adhesiveness and electrical properties by positioning a silver nanomesh and polyvinyl alcohol (PVA) on the skin and then dispersing water to utilize the water solubility of PVA. However, the above method has the disadvantage that the polymer will be dissolved by sweat mainly composed of water, thereby damaging the electrode or the device including the electrode. In addition, the method is limited in that due to the lifting phenomenon that occurs between the attached electrode and the skin caused by movements such as bending the skin, sufficient conformal contact characteristics with the skin cannot be achieved. Therefore, it is necessary for an electrode material that can be attached to the skin to not only have better adhesion, biocompatibility and transparency, but also provide better conformal contact characteristics with the skin without being affected by external environments such as sweat.

[0009] [Citation List]

[0010] (Non-patent document 1) W.-H. Yeo, Y.-S. Kim, J. Lee, A. Ameen, L. Shi, M. Li, S. Wang, R. Ma, SH Jin, Z. Kang, Y. Huang, JA Rogers, Adv. Mater. 2013, 25, 2773 Summary of the invention

[0011] Technical issues

[0012] The object of the present invention is to provide a transparent electrode that can be attached to the skin and a method for manufacturing the same, which transparent electrode has very excellent adhesion to the skin, biocompatibility, light transmittance and conformal contact properties with the skin, while providing significantly improved stability because it will not be dissolved by the external environment such as sweat.

[0013] Another object of the present invention is to provide a transparent electrode that can be attached to the skin and a method for manufacturing the same, which transparent electrode has excellent adhesion so that it can be attached to the skin without a separate adhesive, does not cause skin irritation when peeled off, and allows simple control of electrical properties.

[0014] Another object of the present invention is to provide a wearable electronic device comprising the transparent electrode attachable to the skin.

[0015] Another object of the present invention is to provide a wound healing pad comprising the transparent electrode attachable to the skin.

[0016] Another object of the present invention is to provide a wound healing method using the transparent electrode attachable to the skin.

[0017] Technical Solution

[0018] The skin-attachable transparent electrode according to the present invention comprises an alcohol-soluble biocompatible elastomer matrix and a conductive material network embedded in the matrix, wherein one surface of the biocompatible elastomer matrix is ​​dissolved when in contact with alcohol and conformally coated on the skin.

[0019] In embodiments, a surface of the biocompatible elastomeric matrix may be conformally coated following the shape of the pores of the skin.

[0020] In an embodiment, the conductive material may be one or a combination of two or more selected from metal nanowires, metal nanoparticles, metal nanomesh, carbon nanotubes, graphene-based compounds, graphite, and conductive polymers.

[0021] In an embodiment, the conductive material may include a one-dimensional conductive material.

[0022] In an embodiment, the conductive material may include metal nanowires.

[0023] In embodiments, the biocompatible elastomer may be a thermoplastic polymer having a glass transition temperature of -10°C or less.

[0024] In embodiments, the biocompatible elastomer may include polyurethane.

[0025] In an embodiment, the polyurethane may include a polyether-based diol structural unit.

[0026] In an embodiment, the alcohol may be a C1-3 alcohol.

[0027] In embodiments, the biocompatible elastomer may be water-insoluble.

[0028] In embodiments, the biocompatible elastomer may have a Young's modulus of 500 kPa or less.

[0029] In embodiments, the elongation at break of the biocompatible elastomer may be greater than the elongation at break of the biocompatible elastomer coated with alcohol, and less than the elongation at break of the biocompatible elastomer coated with distilled water.

[0030] In an embodiment, the skin-adhesive transparent electrode may have a light transmittance of 65% or more for 550 nm to 700 nm.

[0031] In embodiments, skin-adhesive transparent electrodes may be used for wound healing via electrical stimulation.

[0032] In embodiments, the wound may be a chronic wound.

[0033] Furthermore, the present invention may provide a wearable electronic device including a transparent electrode attachable to the skin.

[0034] In an embodiment, the wearable electronic device may be a sensor, an electronic skin, a flexible display, or a stretchable display.

[0035] In an embodiment, the wearable electronic device may include a function generator configured to detect a physiological signal and adjust the voltage, frequency, time, or waveform of the electrical stimulation.

[0036] Furthermore, the present invention may provide a wound healing pad comprising a transparent electrode attachable to the skin.

[0037] In embodiments, the wound healing pad may be substantially free of adhesive.

[0038] In embodiments, the wound healing pad may be configured to heal a wound via electrical stimulation.

[0039] In an embodiment, the wound healing pad may include two or more skin-attachable transparent electrodes positioned spaced apart from each other and a power supply unit configured to electrically connect the two or more skin-attachable transparent electrodes.

[0040] In embodiments, the wound healing pad may further include a function generator electrically connected between two or more skin-attachable transparent electrodes.

[0041] In the wound healing pad according to the embodiment, two or more skin-adhesive transparent electrodes may be positioned spaced apart from each other with the wound interposed between the two or more skin-adhesive transparent electrodes.

[0042] In addition, the present invention can provide a method for manufacturing a transparent electrode that can be attached to the skin, the method comprising: forming a self-assembled monolayer film on a substrate; forming a conductive material network on the self-assembled monolayer film; and applying and drying an alcohol-soluble biocompatible elastomer solution on the substrate on which the conductive material network is formed, thereby manufacturing a conductive material network embedded in the alcohol-soluble biocompatible elastomer matrix.

[0043] In an embodiment, forming the self-assembled monolayer may include coating a solution for forming the self-assembled monolayer on a substrate; and annealing the substrate coated with the solution for forming the self-assembled monolayer.

[0044] In an embodiment, the solution for forming the self-assembled monolayer may be an alkoxysilane-based compound substituted with a fluorine group or a chlorosilane-based compound substituted with a fluorine group.

[0045] In an embodiment, the method for manufacturing a skin-attachable transparent electrode may further include separating the conductive material network embedded in the alcohol-soluble biocompatible elastomer matrix from the substrate on which the self-assembled monolayer film is formed.

[0046] In addition, the present invention can provide a wound healing method, comprising: treating a skin area to which a skin-attachable transparent electrode is to be attached with alcohol; attaching the skin-attachable transparent electrode to the skin area treated with alcohol; and applying electrical stimulation to the skin-attachable transparent electrode.

[0047] In a wound healing method according to an embodiment, the skin-attachable transparent electrode may include two or more skin-attachable transparent electrodes, and the two or more skin-attachable transparent electrodes may be positioned spaced apart from each other and the wound site is located between the two or more skin-attachable transparent electrodes.

[0048] In the wound healing method according to the embodiment, the electrical stimulation may be generated by a function generator.

[0049] Beneficial effects

[0050] The skin-attachable transparent electrode according to the present invention not only has very excellent adhesion to the skin, biocompatibility, light transmittance, and conformal contact properties with the skin, but also can significantly improve stability because the skin-attachable transparent electrode will not be dissolved by the external environment such as sweat. Therefore, a wearable electronic device and a wound healing pad with superior performance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 is a schematic diagram of a transparent electrode attachable to the skin according to an embodiment.

[0052] Figure 2 is a schematic diagram of a wound healing pad according to an embodiment.

[0053] Figure 3 is a view showing a method for manufacturing a skin-adhesive transparent electrode according to an embodiment.

[0054] Figure 4 : is a view showing the result of a skin irritation test of the skin-adhesive transparent electrode according to the embodiment.

[0055] Figures 5 to 7 It is a diagram showing the results of a cell culture test.

[0056] Figure 8 Stress-strain curves of PDMS, PVA and PU are shown.

[0057] Fig. 9 are views showing the results of a tensile test performed after spraying ethanol or deionized water on PDMS, PVA, and PU.

[0058] Figures 10 to 13 is a view showing the results of evaluation of the adhesive force of the skin-adhesive transparent electrode according to the embodiment.

[0059] Fig.14 is a SEM image of the electrode according to Example 1.

[0060] Fig.15 is a diagram showing the light transmittance of the electrode according to Example 1.

[0061] Fig.16 is a diagram showing the surface resistance according to Example 1.

[0062] Fig.17 is a view showing changes in electrical characteristics caused by external environments.

[0063] Fig.18 and Fig.19 is a view showing an evaluation result of conformal contact characteristics with the skin after manufacturing the skin-adherable transparent electrode as a strain sensor according to the embodiment.

[0064] Fig. 20 is a diagram showing an experimental method for impedance analysis, and Fig.21 is a diagram showing the results of this experimental method.

[0065] Fig. 22 A schematic diagram of an ECG sensor that can be mounted on an arm.

[0066] Fig.23 is a diagram showing measurement results of the Lead 1 ECG sensor using the electrode according to Example 1.

[0067] Fig.24 is a view showing measurement results of an ECG sensor that can be mounted on one arm.

[0068] Fig.25 is a diagram showing an experimental method for measuring an EMG signal, and Fig.26 is a diagram showing the results of this experimental method.

[0069] Invention method

[0070] The embodiments described in this specification may be modified in many different forms, and the technology according to the implementation is not limited to the embodiments set forth below. In addition, the embodiments of the implementation are provided in order to describe the present disclosure in more detail for those skilled in the art.

[0071] Furthermore, singular forms used in this specification and the appended claims may also include plural forms unless the context indicates otherwise.

[0072] In addition, the numerical range used in this specification includes all values ​​within the range, including the lower limit and the upper limit, the increment logically derived from the form and span of the defined range, all bilaterally limited values, and all possible combinations of the upper limit and the lower limit in the numerical range defined in different forms. Unless otherwise defined herein, values ​​outside the numerical range due to experimental errors or rounding values ​​are also included in the defined numerical range.

[0073] In addition, unless explicitly described to the contrary, the word “include or comprise” and variations such as “includes or comprises” or “including or comprising” will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.

[0074] The present inventors have recognized that the skin-attachable transparent electrode materials of the related art, even if they satisfy properties such as adhesion and light transmittance, are not suitable for application in wearable electronic devices, wound healing pads, etc. due to problems such as dissolution due to sweat and insufficient conformal contact properties with the skin. As a result of repeated studies to solve the above problems, the present inventors have found that a skin-attachable transparent electrode including a conductive material network embedded in an alcohol-soluble biocompatible elastomer matrix solves the above problems and has very excellent adhesion to the skin, biocompatibility and light transmittance, thereby completing the present invention.

[0075] Figure 1 is a schematic diagram of a transparent electrode attachable to the skin according to an embodiment.

[0076] The transparent electrode that can be attached to the skin according to the embodiment of the present disclosure will be described in detail below with reference to the accompanying drawings. The accompanying drawings are provided only as examples to ensure that the technical spirit of the present invention can be fully conveyed to the technicians, and the present invention is not limited to the accompanying drawings shown below and can be implemented in many other forms.

[0077] Reference Figure 1 , a transparent electrode attachable to the skin according to an embodiment of the present invention includes an alcohol-soluble biocompatible elastomer matrix and a conductive material network embedded in the matrix, wherein one surface of the biocompatible elastomer matrix is ​​dissolved when in contact with alcohol and is conformally coated on the skin.

[0078] The transparent electrode that can be attached to the skin according to the embodiment includes a conductive material network embedded in an alcohol-soluble biocompatible elastomer matrix, so that one surface of the biocompatible elastomer matrix is ​​dissolved when in contact with alcohol and can be conformally coated on the skin. In addition, the transparent electrode that can be attached to the skin can have excellent adhesion, so that it can be attached to the skin without a separate adhesive, and therefore does not cause skin irritation problems caused by the adhesive and problems of reduced electrical signal detection capabilities.

[0079] In an embodiment, one surface of the biocompatible elastomeric matrix can be conformally coated along the shape of the pores of the skin. Therefore, the skin-attachable transparent electrode can also provide wearable electronic devices and wound healing pads with improved signal detection capabilities and superior performance.

[0080] In an embodiment, the conductive material may be one or a combination of two or more selected from metal nanowires, metal nanoparticles, metal nanomesh, carbon nanotubes, graphene-based compounds, graphite, and conductive polymers.

[0081] The metal of the metal nanowire, the metal nanoparticle, or the metal nanomesh may include, for example, silver (Ag), gold (Au), platinum (Pt), copper (Cu), aluminum (Al), or an alloy thereof, and in particular, may include silver.

[0082] The conductive polymer may be selected from one or a mixture of two or more of the following: poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), polyethylenedioxythiophene, polyaniline, polypyrrole, polythiophene, poly p-phenylene, poly p-phenylenevinylene, polyacetylene, polydiacetylene, polythiopheneethylene, polyfullerene and derivatives thereof, and preferably, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) may be used, but this is not intended to be limiting.

[0083] In an embodiment, the conductive material may include a one-dimensional conductive material, and preferably may include a metal nanowire. The diameter of the metal nanowire may be, but not limited to, 10 nm to 500 nm, specifically 20 nm to 300 nm, and more specifically 20 nm to 100 nm, and the aspect ratio may be, but not limited to, 60 to 3000, specifically 100 to 1500, and more specifically 300 to 1500.

[0084] In an embodiment, the biocompatible elastomer may be a thermoplastic polymer having a glass transition temperature of -10°C or less, and specifically, the glass transition temperature may be -20°C or less or -30°C or less.

[0085] The biocompatible elastomer may include polyurethane, polyoxyethylene-polybutylene terephthalate copolymer, styrene-butadiene copolymer (styrene-butadiene rubber, SBR), styrene-ethylene-butylene-styrene copolymer (styrene-ethylene-butylene-styrene, SEBS), styrene-ethylene-propylene-styrene copolymer (styrene-ethylene-propylene-styrene, SEPS), styrene-butadiene-styrene copolymer (styrene-butadiene-styrene, SBS), styrene-isoprene-styrene copolymer (styrene-isoprene-styrene, SIS), styrene-isobutylene-styrene copolymer (styrene-isobutylene-styrene, SIBS) or a combination thereof, but is not limited thereto, as long as it is an alcohol-soluble elastomer. Preferably, the biocompatible elastomer may include polyurethane.

[0086] In an embodiment, the polyurethane may include a polyether diol structural unit, and specifically, may include a polytetramethylene ether diol structural unit. This enables the purpose of the present invention to be more preferably achieved due to the property of being soluble in alcohol but insoluble in aqueous solution. The biocompatible elastomer may also include a structural unit derived from an alicyclic isocyanate-based monomer, such as, but not limited to, isophorone diisocyanate or 4,4-dicyclohexylmethane diisocyanate.

[0087] In an embodiment, the alcohol capable of dissolving the biocompatible elastomer may specifically be a C1-3 alcohol, and more specifically ethanol.

[0088] In an embodiment, the biocompatible elastomer can be water-insoluble, so that after the skin-attachable transparent electrode including the biocompatible elastomer is dissolved in alcohol and effectively attached to the skin, it will not be dissolved by water-soluble substances such as sweat or rainwater, thereby enhancing the durability of the product to which the skin-attachable transparent electrode is applied.

[0089] The Young's modulus of the biocompatible elastomer in embodiments may be 500 kPa or less, 400 kPa or less, 300 kPa or less, or 250 kPa or less, and the lower limit may be, for example, 100 kPa or 150 kPa.

[0090] In embodiments, the elongation at break of the biocompatible elastomer may be greater than the elongation at break of the biocompatible elastomer coated with alcohol, and less than the elongation at break of the biocompatible elastomer coated with distilled water.

[0091] In this case, the decrease in the elongation at break of the biocompatible elastomer when alcohol is applied is interpreted as the result of the biocompatible elastomer dissolving in the alcohol, which weakens the bonds between the molecules of the biocompatible elastomer, while the increase in the elongation at break of the biocompatible elastomer when distilled water is applied is interpreted as the result of the biocompatible elastomer not dissolving in the distilled water but forming strong bonds between the molecules of the biocompatible elastomer.

[0092] In an embodiment, the thickness of the matrix may be 100 to 200 μm, specifically 150 to 200 μm, and more specifically 160 to 180 μm. Within the above range, physical properties such as light transmittance and adhesiveness of a transparent electrode attachable to the skin may be achieved.

[0093] In an embodiment, the thickness of the conductive material network may be 10 nm to 500 nm, specifically 10 nm to 250 nm, more specifically 50 nm to 150 nm.

[0094] In an embodiment, the ratio of the thickness of the conductive material network to the thickness of the matrix can be 1: 1000 to 1: 2000, 1: 1500 to 1: 2000, or 1: 1600 to 1: 1800. Within this range, the light transmittance, adhesion, conductivity, etc. of the transparent electrode attachable to the skin and the stability to the external environment can be further improved.

[0095] In an embodiment, the conductive material network can be embedded in the matrix to contact one surface of the matrix, which surface of the matrix is ​​dissolved when in contact with alcohol and is conformally coated on the skin, which causes the conductive material network to be positioned in the direction of the surface in contact with the skin, thereby further improving the signal detection capability.

[0096] When the conductive material network is embedded in the matrix to contact one surface of the matrix, the conductive material network can be completely or partially embedded in the matrix, and preferably can be partially embedded. More preferably, the conductive material network can be exposed on one surface of the matrix, and the conductive material network can be unexposed on another surface of the matrix. This enables the surface portion of the conductive material network exposed to be attached to the skin to enhance electrical properties, thereby enabling more effective detection of physiological signals or improving healing effects through electrical stimulation.

[0097] In an embodiment, the skin-attachable transparent electrode may have a light transmittance of 65% or more or 70% or more for a wavelength range of 550 nm to 700 nm, and the upper limit thereof may be, for example, 85% or 90%.

[0098] In an embodiment, a transparent electrode attachable to the skin can be used to heal wounds by electrical stimulation, where the skin and subcutaneous tissue are damaged by external stimulation. The wounds may include minor wounds and chronic wounds that can heal naturally, and in particular, the wounds may be chronic wounds.

[0099] The present invention provides a wearable electronic device comprising the transparent electrode as described above which can be attached to the skin.

[0100] In an embodiment, the transparent electrode attachable to the skin can be applied to various sensors (including strain sensors, temperature sensors, pressure sensors, optical sensors, vibration sensors and biosensors) and various wearable electronic devices (e.g., electronic skin, flexible displays and stretchable displays), and in particular, can be applied to wearable electronic devices attachable to the body designed for the curved surface of the skin, but this does not limit its application in clothing-type or accessory-type wearable electronic devices.

[0101] In an embodiment, the sensor may include a function generator that detects physiological signals and adjusts the voltage, frequency, time or waveform of the electrical stimulation, wherein the physiological signals may include but are not limited to electrocardiogram, electromyogram and body movement. The stimulation may have a form such as a sine wave, a pulse or a square wave.

[0102] In addition, the present invention provides a wound healing pad comprising the transparent electrode as described above which can be attached to the skin. Figure 2 is a schematic diagram of a wound healing pad according to an embodiment, referring to Figure 2 A wound healing pad according to the present disclosure is described in detail.

[0103] The wound healing pad according to the embodiment may include two or more transparent electrodes 10 that are attached to the skin and are positioned at intervals from each other and a power supply unit 20 that electrically connects the two or more transparent electrodes that are attached to the skin. Specifically, the two or more transparent electrodes may be positioned at intervals from each other and the wound 1 is interposed between the two or more transparent electrodes.

[0104] In an embodiment, the wound healing pad may further include a function generator electrically connected between two or more transparent electrodes attachable to the skin, wherein the function generator is used to adjust the voltage, frequency, time or waveform of the electrical stimulation. By adjusting the characteristics of the electrical stimulation, the extent of treatment can be determined according to the location, size, depth and shape of the wound and the patient's recovery status.

[0105] In an embodiment, the wound healing pad can be substantially free of adhesive by including the transparent electrode that can be attached to the skin. More specifically, including an alcohol-soluble biocompatible elastomer significantly improves the adhesion to the skin, which enables effective attachment to the skin without the need for a separate adhesive and does not cause the problem of skin irritation and reduced electrical signal detection capability caused by the adhesive.

[0106] It should be noted that the description "substantially free of adhesive" means that the content of adhesive does not significantly affect the operation of the transparent electrode or wound healing pad that can be attached to the skin, and does not exclude the inclusion of trace amounts of adhesive that may exist as impurities or for other known supplementary effects. Specifically, relative to the total weight of the wound healing pad, the content of the adhesive may be 1 wt% or less, 0.1 wt% or less, 0.01 wt% or less, or 0.001 wt% or less, with a lower limit of 0 wt% or more.

[0107] In an embodiment, the wound healing pad may heal a wound by electrical stimulation, and the wound may specifically be a chronic wound.

[0108] Figure 3 is a view showing a method for manufacturing a transparent electrode attachable to the skin according to an embodiment. Figure 3 Methods for making skin-adhesive transparent electrodes are described in detail.

[0109] A method for manufacturing a transparent electrode that can be attached to the skin according to an embodiment of the present invention includes: a first step of forming a self-assembled monolayer film on a substrate; a second step of forming a conductive material network on the self-assembled monolayer film; and a third step of applying and drying an alcohol-soluble biocompatible elastomer solution on the substrate on which the conductive material network is formed, thereby manufacturing a conductive material network embedded in the alcohol-soluble biocompatible elastomer matrix.

[0110] The first step is a step of forming a self-assembled monolayer film on a substrate, which may include a transparent material capable of transmitting light, and may include, for example, a silicon substrate, a glass substrate, or a polymer substrate, but is not limited thereto.

[0111] The silicon substrate may include a single crystal silicon substrate or a p-Si substrate; the glass substrate may be made of one or a combination of alkali silicate glass, non-alkali glass or quartz glass, but is not limited thereto and may be made of various other materials.

[0112] The polymer substrate may be made of one or a combination of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), and polyurethane, but is not limited thereto, and may be made of various other materials. However, the polymer substrate is not necessarily limited thereto as long as it has sufficient transparency and flexibility for a transparent flexible display.

[0113] In an embodiment, the first step may include the steps of coating a solution for forming a self-assembled monolayer film on a substrate; and annealing the substrate coated with the solution for forming a self-assembled monolayer film.

[0114] Specifically, the solution for forming the self-assembled monolayer film may be a solution containing a silane-based compound. The silane-based compound may be Indicates that R 1 is hydroxy, C1-C4 alkoxy or halogen, R 2 It is C1-C 20 Alkyl, C1-C 20 Carboxyalkyl, C1-C 20 Aminoalkyl, C1-C 20 Perfluoroalkyl, C1-C 20 Fluoroalkyl or C2-C 20 an acryloyloxyalkyl group, and n is an integer of 1 to 3. Specifically, the silane compound may be an alkoxysilane compound or a chlorosilane compound, and more specifically, an alkoxysilane compound substituted with a fluorine group or a chlorosilane compound substituted with a fluorine group, so that the surface can be treated as a hydrophobic surface.

[0115] Specifically, the annealing may be performed at 100°C to 180°C or 100°C to 150°C.

[0116] The second step is a step of forming a conductive material network on the self-assembled monolayer film, and the above description can be applied to the conductive material. Specifically, the second step may include a step of coating a conductive material solution on the self-assembled monolayer film. For example, the coating method may use spin coating, spray coating, inkjet coating, slit coating, deep coating, etc., but there is no particular limitation.

[0117] The third step is to apply and dry an alcohol-soluble biocompatible elastomer solution on the substrate formed with the conductive material network, thereby producing an alcohol-soluble biocompatible elastomer matrix embedded with the conductive material network. The above description can be applied to alcohol-soluble biocompatible elastomers. The applying step can be performed by various methods of forming a thin film using a solution process, and preferably can be performed by at least one method selected from spin coating, drop casting, dip coating, spray coating, casting, screen printing, inkjet printing and microcontact printing, and more preferably can be performed by drop casting.

[0118] In an embodiment, the method for manufacturing a skin-attachable transparent electrode may further include a fourth step of separating the conductive material network embedded in the alcohol-soluble biocompatible elastomer matrix from the substrate on which the self-assembled monolayer film is formed.

[0119] According to an embodiment of the present invention, a wound healing method includes the following steps: treating a skin portion to which a skin-attachable transparent electrode is to be attached with alcohol; attaching the skin-attachable transparent electrode to the skin portion treated with alcohol; and applying electrical stimulation to the skin-attachable transparent electrode.

[0120] In an embodiment, the skin-adhesive transparent electrode may include two or more skin-adhesive transparent electrodes positioned spaced apart from each other and the wound site is interposed between the two or more skin-adhesive transparent electrodes.

[0121] In an embodiment, the electrical stimulation may be generated by a function generator.

[0122] The wound healing method according to the embodiment enables one surface of the biocompatible elastomer matrix contained in the above-mentioned transparent electrode that can be attached to the skin to be dissolved and conformally attached to the skin when in contact with alcohol to improve the signal detection capability, thereby enabling the wound to heal more effectively. In addition, by using a transparent electrode having excellent adhesion so that it can be attached to the skin without a separate adhesive, the wound is healed without the problem of skin irritation caused by the adhesive and the reduction of the electrical signal detection capability. DETAILED DESCRIPTION

[0123] Examples and experimental examples will be specifically described in detail below. However, the examples and experimental examples described below are only partially illustrative, and the technology described in this specification is not to be construed as being limited thereto.

[0124] <Example 1> Preparation of transparent electrodes that can be attached to the skin

[0125] First, a self-assembled monolayer (SAM) was formed on a Si wafer substrate by evaporating a trichloro(1H,1H,2H,2H-perfluorooctyl)silane (Sigma Aldrich) solution in a vacuum chamber where the Si wafer substrate was placed and annealing at 135° C. for 1 hour.

[0126] A dispersion was prepared by dispersing 0.63 wt % silver nanowires (Novarials) having an average diameter of 30 nm and a length of 30 μm in ethanol, evaporating the dispersion, and then spraying 0.3 ml on a substrate (2.5 cm×2.5 cm) on which a SAM was formed to form a silver nanowire network on the SAM. Specifically, the distance between the nozzle and the substrate was 15 cm, and the spray rate was 0.3 ml min -1 Spray at a speed of

[0127] Then, 10 wt % of a polyether-based hydrophilic PU (Hydromed D4 available from AdvanSource Biomaterials) was dissolved in a solvent having a weight ratio of ethanol to distilled water of 19:1 to prepare a PU solution. The PU solution was drop-cast onto the substrate having the silver nanowire network formed thereon, and then dried at room temperature for 4 hours to prepare a PU matrix having the silver nanowire network embedded therein.

[0128] Finally, the prepared PU matrix having the silver nanowire network embedded therein was separated from the substrate having the SAM formed thereon at room temperature to prepare a transparent electrode (denoted as Ag / PU or TSE in the figure) that can be attached to the skin.

[0129] <Experimental Example 1> Biocompatibility Evaluation

[0130] Biocompatibility assessment was performed by skin irritation test and cell culture test.

[0131] For the skin irritation test, the electrodes prepared in Example 1 were attached to the skin and then removed after 4 hours, 8 hours, and 12 hours to measure the degree of skin irritation. Figure 4 See Figure 4 , no erythema, residue, or pain occurred at the site where the electrode prepared in Example 1 was removed (indicated by the white dotted line), which confirms that the transparent electrode attachable to the skin according to the embodiment has low skin irritation.

[0132] For the cell culture test, the electrodes prepared in Example 1 (or Ag / PU), polyurethane (PU; Hydromed D4 available from AdvanSource Biomaterials) and poly(dimethylsiloxane) (PDMS; Dow Corning Sylgard 184 Elastomer Kit) were added, respectively, and mouse fibroblasts (L929) were cultured. The cell culture medium was 2 ml of Dulbecco'smodified Eagle's medium (DMEM) with high glucose containing 10% fetal bovine serum (FBS) and 1% antibiotics, and the cells were observed for 3 days under culture conditions of 37°C, 5% CO2 and 95% humidity by daily live / dead cell staining (n=1), cell activity test by CCK8 assay (n=2) and proliferation test by DNA content assay (PicoGreen, n=3). In addition, the positive control was cultured only in the cell culture medium, and the negative control was cultured in the cell culture medium supplemented with antimycin A. The results are respectively Figures 5 to 7 See Figure 5 , Fluorescent live / dead staining images showed regular cell morphology similar to the positive control after 3 days in all cases, indicating that the material is highly cytocompatible and non-toxic to cells. Figure 6 For PDMS and PU, the cell viability was over 80% starting from day 1, while for Ag / PU, the cell viability was below 70% on day 1 but continued to increase over time. In this case, cell viability refers to the number of cells grown on each sample surface (N A ) and the number of cells grown in the positive control (N B ) ratio (N A / N B ). Reference Figure 7 All cases showed an increasing trend of DNA concentration within 3 days, confirming the biocompatibility in terms of cell proliferation.

[0133] <Experimental Example 2> Mechanical Properties Evaluation

[0134] To evaluate the mechanical properties, PDMS, PVA, and PU were prepared into a size of 2 cm × 0.5 cm and subjected to tensile tests. The tensile tests were performed using a universal testing machine (UTM, WL2100C, WithLab) with a 1 kgf load cell. Figure 8 Shown in. Figure 8 The stress-strain curves for each polymer material are shown. Figure 8 , the Young’s modulus of PU is lower than 225 kPa, which is much lower than that of PDMS and PVA.

[0135] In addition, to confirm the effect of solvent on each polymer material, tensile tests were performed after spraying ethanol or deionized water. Fig. 9 See Fig. 9 , the elongation at break of PDMS did not show a decrease due to deionized water or ethanol, indicating that deionized water and ethanol cannot change the main polymer chain of PDMS. In contrast, PVA is soluble in both deionized water and ethanol, so its elongation at break drops from 120% to 70%, and its tensile strength weakens. Only when treated with ethanol, the elongation at break of PU shows a faster decrease from 800% to 700%, while treatment with deionized water does not destroy the covalent bonds in the polymer. It can be seen that the PU material is soluble in alcohol but not in deionized water, so it can be used stably even in external environments such as sweat, making it suitable for use as an electrode that can be attached to the skin.

[0136] <Experimental Example 3> Adhesion Evaluation

[0137] To evaluate the adhesion of the electrode, a 180° peel test (ASTM F2256) was performed on artificial skin and a 90° peel test (ASTM D6862) was performed on a human forearm using a UTM (WL2100C, WithLab) with a 1 kgf load cell. Micropig Franz Cell Membrane (FCM) available from APURES was used as the artificial skin, and the electrode (50 mm×50 mm) prepared in Example 1 was placed between two FCMs, ethanol was sprayed on the electrode, and the electrode was attached by light pressure. Then, the electrode was placed at 50 mm min. -1 The electrode prepared in Example 1 was peeled off at a peeling speed of Fig.10 In addition, a 90° peel test was performed on a human forearm using the electrode with a size of 50 mm × 150 mm prepared in Example 1. Fig.11 See Fig.10 and Fig.11 The electrode prepared in Example 1 exhibited a resistance of 0.08 N cm -1 The interface toughness of 0.05N cm -1 In addition, the same test was performed using a commercially available Tegaderm film. The interfacial toughness values ​​measured for Tegaderm on artificial skin and on human forearm were 0.008 N cm -1 and 0.007N cm -1 . According to the EcoFlex (00-30, Smooth-On, <0.04N cm -1 ) and PDMS (Sylgard 184, Dow Corning, <0.04N cm-1 ) of the elastomer, the skin-attachable electrode according to the embodiment exhibits excellent adhesion properties on both artificial skin and human skin.

[0138] In addition, tensile tests were conducted on FCM with a contact area of ​​30 mm × 30 mm and on the back of the hand with a contact area of ​​50 mm × 50 mm. Fig.12 and Fig.13 See Fig.12 and Fig.13 The electrodes prepared in Example 1 showed 0.3N cm -2 and 0.2N cm -2 tensile strength.

[0139] <Experimental Example 4> Evaluation of light transmittance and electrical characteristics

[0140] The transmittance was measured by UV-visible spectroscopy. The sheet resistance was measured by a four-point probe. In addition, a field emission scanning electron microscope (FE-SEM, IT500, JEOL Co., Ltd.) was used to analyze the electrode after peeling from the skin. In addition, in order to evaluate the chemical stability, the changes in electrical properties due to the external environment were observed. Specifically, the skin-attachable electrode according to Example 1 was exposed to deionized water, pH 4.01 buffer (Tokuyama reagent), pH 6.86 buffer (Tokuyama reagent) and ambient air (ambient conditions) to measure the rate of change of resistance value. The resistance was measured every 4 hours for 12 hours using a digital multimeter (Fluke). The results are shown in Table 1. Figures 14 to 17 Shown in.

[0141] Fig.14 is a SEM image of the electrode according to Example 1. Fig.14 , it can be confirmed that the silver nanowires stably penetrated and embedded in the polyurethane phase after being separated from the substrate.

[0142] Note that the amount of silver nanowires used was adjusted by applying a spray coating method as a coating method, which enables adjustment of light transmittance and surface resistance. Fig.15 and Fig.16 The light transmittance and surface resistance of the electrode according to Example 1 are shown respectively. Fig.15 and Fig.16 It can be confirmed that the sample with a surface resistance of 30 ohm sq-1 shows a transmittance of about 70% at a wavelength of 550 nm and is comparable to the electrode coated with silver nanowires on a glass substrate ( Fig.16 Compared with the electrodes embedded with silver nanowires in PU (indicated as “bare” in Fig.16The surface resistance of the Ag nanowires (indicated by “embedded” in Figure 1) increased to 70 ohm sq⁻¹. This is because mechanical stimulation was applied to the PU when the PU electrode in which the Ag nanowires were embedded was separated from the substrate.

[0143] Fig.17 is a diagram showing changes in electrical characteristics caused by external environment. Fig.17 After exposure to deionized water, pH 4.01 buffer, pH 6.86 buffer and ambient air for 12 hours (h), the change in relative resistance value (R / Rt=0) is less than 50%, preferably less than 30%.

[0144] <Experimental Example 5> Application to strain sensors

[0145] The skin-attachable transparent electrode (3 cm×0.5 cm) according to Example 1 was fabricated as a strain sensor for motion detection, and its conformal contact characteristics with the skin were confirmed. The AgNW / PDMS electrode was used as a reference electrode. The AgNW / PDMS electrode (3 cm×0.5 cm) was prepared by spin coating a dispersion on a glass substrate on which AgNWs were sprayed at 300 rpm for 15 s, followed by curing at 90°C for 1 hour, wherein the dispersion was prepared by mixing a polydimethylsiloxane main agent and a polydimethylsiloxane curing agent in a weight ratio of 10:1. The change in the resistance value of the finger and the neck was measured using a digital multimeter (DMM 6500, Keithley). Fig.18 and Fig.19 See Fig.18 It can be confirmed that the AgNW / PDMS electrode produced gaps when the finger was bent and did not adhere to the wrinkles. No change in resistance was observed during the finger bending cycle (in Fig.18 In contrast, the electrode according to Example 1 was able to achieve conformal contact with the generated wrinkles by redissolving the PU matrix on the surface by ethanol to effectively send motion information to the strain sensor. In addition, the change in resistance was clearly observed during the finger flexion cycle. Fig.19 The electrode is mounted on the uvula to detect the drinking action. Similarly, the change in resistance when drinking water can be clearly observed (in Fig.19 indicated by arrows).

[0146] <Experimental Example 6> Evaluation of electrophysiological characteristics

[0147] Impedance analysis and ECG and EMG signal monitoring were performed to evaluate electrophysiological properties. By first preparing the electrodes (2 cm×2 cm) according to Example 1 and commercial Ag / AgCl gel electrodes (1.5 cm×2 cm) (2223H, 3M), as Fig. 20Impedance analysis was performed by attaching both electrodes to the arm at 1 cm intervals and connecting the electrodes to an electrochemical impedance spectrometer (SP-300, BioLogic) at 100 mV and a frequency of 1 Hz to 1 MHz. The results of the impedance analysis are shown in Fig.21 See Fig.21 , it can be seen that the electrode according to Example 1 exhibits lower impedance than the Ag / AgCl electrode. Therefore, the skin-attachable transparent electrode according to the embodiment can improve the interface impedance characteristics.

[0148] Next, ECG signal measurements were performed by connecting a data acquisition board (heart rate monitoring sensor SKU: SEN 0213 from DFRobot) to the Arduino UNO and using commercial Ag / AgCl electrodes as reference electrodes. The measurements were performed in two ways.

[0149] The first method was a conventional lead 1 ECG measurement, which was performed by attaching the electrodes according to Example 1, the Ag / AgCl electrodes, and the dry Ag / AgCl electrodes to the right arm, left arm, and left leg. Fig.23 The dry Ag / AgCl electrode was dried for 2 hours under ambient air conditions before attachment, and since the hydrogel portion of the electrode had been dried, the signal-to-noise ratio was lower. In contrast, the electrode according to Example 1 ( Fig.23 The TSE in Figure 5 shows a high signal-to-noise ratio similar to that of the Ag / AgCl electrode that has not undergone a drying process.

[0150] The second method is to design Fig. 22 Specifically, the two electrodes according to Example 1 and the reference electrode are attached to the right arm, and one of the electrodes according to Example 1 is touched with a finger of the left hand to detect an ECG signal. Fig.24 See Fig.24 , the signal measured by the ECG sensor mounted on one arm has the form of a commonly obtained PQRSTU ECG signal, but exhibits a deeper TU valley than the TU valley measured by a conventional lead 1 ECG.

[0151] Finally, EMG signal measurement was performed by connecting a data acquisition board (SZH-HWS010) to an Arduino UNO and using a commercial Ag / AgCl electrode as a reference electrode, and attaching the two electrodes according to Example 1 to the forearm and the reference electrode to the upper arm, as Fig.25 The results of EMG signal measurement are shown in Fig.26 See Fig.26, it can be seen that the electrode according to Example 1 is able to measure EMG signals with performance similar to that of the Ag / AgCl electrode.

[0152] It can be seen that the transparent electrode attachable to the skin according to the embodiment can measure electrophysiological signals well, and there is no problem associated with commercial Ag / AgCl electrodes, such as performance degradation due to drying. In addition, the transparent electrode attachable to the skin according to the embodiment can be attached to the skin without using an adhesive that causes skin irritation and degradation of electrical properties, has the advantages of excellent biocompatibility, light transmittance and skin flexibility, and can operate stably even in a sweating state.

[0153] In the above, although the present disclosure has been described through specific matters and limiting embodiments in this specification, they are provided only to help a more general understanding of the present disclosure. Therefore, the present disclosure is not limited to these embodiments, and those skilled in the art can make various modifications and changes to the contents of the present disclosure that are subordinate to this specification.

[0154] Therefore, the spirit described in this specification should not be limited to the above-mentioned embodiments, and the appended claims and all modifications equivalent to or equivalent to the claims are intended to fall within the scope and spirit described in this specification.

[0155] [reference numerals list]

[0156] 10: Transparent electrodes that can be attached to the skin

[0157] 20: Power supply unit

[0158] 1: Wound.

Claims

1. A transparent electrode attachable to the skin, comprising: an alcohol-soluble biocompatible elastomeric matrix; as well as a network of conductive material embedded in said matrix, Therein, one surface of the biocompatible elastomeric matrix is ​​dissolved when in contact with alcohol and is conformally coated on the skin.

2. The skin-attachable transparent electrode according to claim 1, wherein: One surface of the biocompatible elastomeric matrix is ​​conformally coated along the shape of the pores of the skin.

3. The skin-attachable transparent electrode according to claim 1, wherein: The conductive material is one or a combination of two or more selected from metal nanowires, metal nanoparticles, metal nanonets, carbon nanotubes, graphene-based compounds, graphite and conductive polymers.

4. The skin-attachable transparent electrode according to claim 1, wherein: The conductive material includes a one-dimensional conductive material.

5. The skin-attachable transparent electrode according to claim 4, wherein: The conductive material includes metal nanowires.

6. The skin-attachable transparent electrode according to claim 1, wherein: The biocompatible elastomer is a thermoplastic polymer having a glass transition temperature of -10°C or less.

7. The skin-attachable transparent electrode according to claim 1, wherein: The biocompatible elastomer includes polyurethane.

8. The skin-attachable transparent electrode according to claim 7, wherein: The polyurethane includes polyether diol structural units.

9. The skin-attachable transparent electrode according to claim 1, wherein: The alcohol is a C1-3 alcohol.

10. The skin-adhesive transparent electrode according to claim 1, wherein: The biocompatible elastomer is insoluble in water.

11. The skin-attachable transparent electrode according to claim 1, wherein: The biocompatible elastomer has a Young's modulus of 500 kPa or less.

12. The skin-adhesive transparent electrode according to claim 1, wherein: The elongation at break of the biocompatible elastomer is greater than the elongation at break of the biocompatible elastomer coated with alcohol, and is less than the elongation at break of the biocompatible elastomer coated with distilled water.

13. The skin-adhesive transparent electrode according to claim 1, wherein: The skin-adhesive transparent electrode has a light transmittance of 65% or more at a wavelength of 550 nm to 700 nm.

14. The skin-adhesive transparent electrode according to claim 1, wherein: The skin-adhesive transparent electrodes are used for wound healing via electrical stimulation.

15. The skin-adhesive transparent electrode according to claim 14, wherein: The wound is a chronic wound.

16. A wearable electronic device comprising the skin-attachable transparent electrode according to any one of claims 1 to 13.

17. The wearable electronic device according to claim 16, wherein: The wearable electronic device is a sensor, an electronic skin, a flexible display or a stretchable display.

18. The wearable electronic device according to claim 16, wherein: The wearable electronic device includes a function generator configured to detect a physiological signal and adjust a voltage, a frequency, a time or a waveform of electrical stimulation.

19. A wound healing pad comprising the skin-adhesive transparent electrode according to any one of claims 1 to 15.

20. The wound healing pad according to claim 19, wherein: The wound healing pad is substantially free of adhesive.

21. The wound healing pad according to claim 19, wherein: The wound healing pad is configured to heal a wound through electrical stimulation.

22. The wound healing pad according to claim 19, further comprising: Two or more skin-attachable transparent electrodes are positioned spaced apart from each other and a power supply unit configured to electrically connect the two or more skin-attachable transparent electrodes.

23. The wound healing pad according to claim 22, further comprising: A function generator is electrically connected between the two or more skin-attachable transparent electrodes.

24. The wound healing pad of claim 22, wherein: The two or more skin-adhesive transparent electrodes are positioned spaced apart from each other and the wound is interposed between the two or more skin-adhesive transparent electrodes.

25. A method for manufacturing a transparent electrode attachable to skin, the method comprising: forming a self-assembled monolayer film on a substrate; forming a conductive material network on the self-assembled monolayer; as well as An alcohol-soluble biocompatible elastomer solution is applied and dried on the substrate formed with the conductive material network, thereby manufacturing a conductive material network embedded in the alcohol-soluble biocompatible elastomer matrix.

26. The method of claim 25, wherein: The forming of the self-assembled monolayer film includes: coating a solution for forming the self-assembled monolayer film on a substrate; and annealing the substrate coated with the solution for forming the self-assembled monolayer film.

27. The method of claim 26, wherein: The solution for forming the self-assembled monolayer is an alkoxysilyl compound substituted with a fluorine group or a chlorosilyl compound substituted with a fluorine group.

28. The method of claim 25, further comprising: The conductive material network embedded in the alcohol-soluble biocompatible elastomer matrix is ​​separated from the substrate on which the self-assembled monolayer is formed.

29. A wound healing method, comprising: treating the skin area to which the skin-adhesive transparent electrode is to be attached with alcohol; attaching the skin-adhesive transparent electrode according to any one of claims 1 to 15 to the skin site treated with alcohol; and Electrical stimulation is applied to the skin-attachable transparent electrode.

30. The wound healing method according to claim 29, wherein: The skin-attachable transparent electrode includes two or more skin-attachable transparent electrodes, the two or more skin-attachable transparent electrodes are positioned spaced apart from each other and the wound site is between the two or more skin-attachable transparent electrodes.

31. The wound healing method according to claim 29, wherein: The electrical stimulation is generated by a function generator.